Study of problems in utilizing the functions of Kasinan protected forest between local residents and "Sadar Alas" community groups - Mohammad Sulthon Neagara; Fuad Muhammad; Maryono Maryono (Journal of Bioresources and Environmental Sciences, 2024)
Understanding disputing styles is very important for solving a problem. The purpose of this research is to examine descriptively the problems in the Kasinan protected forest and to identify the conflicting styles of each party so that an appropriate resolution of the problems can be developed. This research was conducted in the protected forest of Kasinan, precisely in Pesanggrahan Village, Batu City. Data collection was carried out qualitatively, namely through interviews, observation, and documentation. The analysis used adapts the Disputing Style Analysis (AGATA). The results of the research show that the problems in the Kasinan protected forest stem from the use of the forest for tourism by relying on water sources from the Kasinan protected forest. The impact was a decrease in the discharge of water flowing into the rice fields and residents' homes, resulting in protests from residents. Actors involved in the problem include residents of Pesanggrahan village, HIPPA-HIPPAM, Pesanggrahan Village Government, Sadar Alas community, Perhutani KPH Malang, BKPH Pujon, and Walhi. Each party has various problems, including environmental beauty, reducing water discharge, and tourism interests. Communities are the most disadvantaged because they feel the impact directly. Each side has a different style of conflict. However, especially for residents of the Sadar Alas community, they have a competitive dispute style. So, in an accommodation style, the village government formed a team of Kasinan Forest Utilization Problem Resolution Facilities and held meetings including villagers, HIPPA-HIPPAM, Alas Awareness Community, Perhutani, and the Mayor of Batu City to negotiate and facilitate the proposal for zoning based on local policies so that the environment is beautiful. and the tour continues. So support from parties who have full authority, such as the Mayor of Batu City, is needed in order to realize a resolution to the conflict.